How can leaders develop and maintain high achieving elementary schools? A single case study exploring collective teacher efficacy, principal leadership, and high reliability organization principles - Ernst, Susan, author; Cooner, Donna, advisor; Fothergill, Wendy, committee member; O'Donnell-Allen, Cindy, committee member; Sebald, Ann, committee member (Colorado State University. Libraries, 2021)
With the issue of student achievement at the core of educational policy, it is essential to determine how to create school environments in which all students achieve. Research indicates collective teacher efficacy is a primary factor affecting student achievement, yet educational research also points to the importance of principal leadership in fostering and maintaining school cultures of success. Furthermore, it seems there are lessons to be learned from looking beyond the scope of educational literature into organizational learning as a way to engage in systematic decision making. Though collective teacher efficacy and principal leadership have been the primary focus of such research, employing high reliability organization principles is an emerging area of educational research. The included sections serve to review the literature across collective teacher efficacy, principal leadership, and high reliability organization principles within a systems thinking approach; critically analyze and employ research methods from scholars in the field of education; and link theory to practice while grappling with the issue of student achievement in a complex educational context. A QUAL+quan mixed methods approach guided the research to explore teacher and principal perceptions of collective teacher efficacy, examine leadership actions to foster collective teacher efficacy among staff, and link leadership actions to high reliability organization principles.
Keywords: collective teacher efficacy (CTE); principal leadership; high reliability organization principles (HRO); educational leadership; organization theory; elementary education; education